(untitled) (FULafia Journal of Science and Technology, 2021)
Wind energy is a renewable source of energy which has a definite place in the future of the generation of electricity. To harness the energy from the wind, a wind turbine is employed. Wind turbines assist in the production of power to compensate for the moderate intensity of the breeze to drive a generator. With the use of wind turbines, the energy in the wind can be converted into electrical energy. A small scale horizontal wind turbine was constructed with readily available and locally sourced materials. The height of the turbine was varied from 3 to 6 meters and two different locations in Ilorin, a tropical region, was used to observe how the turbine generates electricity via the wind turbine. The dam site, one of the locations, gives very high wind speed which in turn produces high open circuit voltage of around 4000 mV. Electrical energy generation from wind energy is observed to be largely dependent, not only on the electric motor used, but on the wind speed available for the turbine.